Magnetic subfabrics of the Whistle Offset dyke and embayment, Sudbury Impact Structure, Sudbury, Ontario - Giroux, Laura Allison (University of Ottawa (Canada), 2005)
Quartz-diorite Offset dykes from the 1850 Ma Sudbury Impact Structure stem from the Sudbury Igneous Complex (SIC) and extend into the footwall rocks in radial and concentric patterns with respect to the SIC. The dykes formed by emplacement of magma derived from the impact melt body into radial and concentric fractures generated in the country rock by the hypervelocity meteorite impact. The NE-striking Whistle Offset dyke extends from the northeast corner of the SIC, and is connected to the SIC by the Whistle embayment structure. A suite of oriented specimens was collected from 20 sites in the Whistle Offset dyke and the embayment, in order to determine the emplacement flow pattern within the dyke, the embayment, and the hosted massive sulfide deposits. The emplacement flow pattern was studied by using magnetic anisotropy measurements in order to infer the petrofabrics, and the subfabrics, defined by different mineral populations. The magnetic anisotropy methods included the anisotropy of magnetic susceptibility (AMS), the anisotropy of anhysteretic remanence (AAR) and the anisotropy of partial anhysteretic remanence (ApAR). The complex magnetic mineralogy of the sample suite was examined using measurements of partial anhysteretic remanence (PAR) acquisition, alternating-field demagnetization and thermal demagnetization, in addition to petrographic and scanning electron microscope (SEM) studies. The subfabrics which are interpreted to record the flow pattern in the Whistle Offset dyke, are defined by low coercivity coarse-grained magnetite, interpreted to be of primary igneous origin. The fabrics are suggestive of lateral (horizontal) injection of the magma and subsequent sinking of molten massive sulfide bodies through the still unsolidified dyke. Sinking of the massive sulfides is recorded by moderately plunging to vertical magnetic lineations. Steeply plunging lineations elsewhere in the Offset dykes may also indicate the presence of sunken massive sulfides in the subsurface.
Keywords: Geology.